ANALIZA MOTIVACIJE TURISTA ZA PROMOCIJU DESTINACIJE PUTEM EWOM-A: FOKUS NA GASTRONOMSKE MANIFESTACIJE - Vukolić, Dragan; Gajić, Tamara; Popović, Andjelka; Cilić, Marko (Turističko poslovanje, 2024)
Gastronomy plays a significant role in the cultural experience of everyday life, offering tourists a unique way to explore different aspects of a destination. Culinary experiences often serve as a key factor in the decision-making process when choosing travel destinations. During 2023 and 2024, the authors conducted a study at four major events in rural areas of Serbia: Kulen Festival in Erdevik, Bacon Festival in Kačarevo, Cabbage Festival in Mrčajevci, and Bean Festival in Čenej, surveying a total of 235 visitors. The aim of the research was to analyze the motivation of tourists at gastronomic events with the goal of promoting the destination through eWOM. The results showed that five factors influence tourists at gastronomic events to be motivated to recommend and promote the tourist destination through eWOM. The findings of this study indicate a significant potential for the development of gastronomic tourism in rural tourist destinations in Serbia. The practical implications of this research suggest that organizers of gastronomic events should focus on enhancing the tourist experience in order to encourage more positive eWOM, thereby effectively promoting destinations and attracting a larger number of tourists.
Keywords: мотивација; рурална дестинација; гастрономске манифестације; eWOM